2015
DOI: 10.1007/s00520-015-2741-6
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between palliative care consultation service and end-of-life outcomes

Abstract: This study confirms the outcomes of PCCS and highlights the important predictors for patients at PCCS termination. These factors can be targeted to improve and enhance the quality of PCCS rendered in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Obermeyer et al reported that the female was associated with hospice enrollment in poor-prognosis cancer patients [ 22 ]. Another study showed that there were more men than women in patients receiving palliative care consultation service [ 23 ]. Until now, there were no consistent findings in gender distribution due to very limited studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obermeyer et al reported that the female was associated with hospice enrollment in poor-prognosis cancer patients [ 22 ]. Another study showed that there were more men than women in patients receiving palliative care consultation service [ 23 ]. Until now, there were no consistent findings in gender distribution due to very limited studies.…”
Section: Discussionmentioning
confidence: 99%
“…The same finding is also mentioned by some past studies, indicating that patients cared by medical oncologists were significantly more likely to enroll in hospice than patients cared by other specialties. [ 22 , 23 ] Obermeyer et al assumed that the medical oncologists may make better prognostic estimates and may be more effective in discussing hospice care with patients when compared with other specialties [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…They collaborated with primary health professionals to mainly provide advice, support, and guidance regarding palliative care [ 4 , 5 ]. A study has confirmed the outcomes of PCCS, which revealed patients who received PCCS, received better symptom management, spiritual support and earlier development of resuscitation plans [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even though the optimal time point and extent of PC is still in debate [2], there is little doubt of a general benefit [3]. It has shown to improve patients' quality of life and symptom control [4], to reduce psychological distress for patients and family caregivers [5,6], and to decrease health care costs due to for example less intensive care unit treatment [7]. It is anticipated that many patients facing an advanced, life-limiting disease would benefit from PC, and only a minority is provided with such service [8].…”
Section: Introductionmentioning
confidence: 99%
“…Improvement of mental well-being after IPCC seems to be based, inter alia, on spiritual care and high quality communication with patients and their family caregivers [24,25]. It leads to strengthened relationships and improved emotional stability especially concerning confrontation with death [4]. Additionally, IPCC has shown to enhance patients' awareness of the disease including its prognosis [26].…”
Section: Introductionmentioning
confidence: 99%